Plastic as the Fill-In Material for Pothole Repairing - Jamahuri, Nadira; NASRADEEN ALI KHALIFA MILAD (Recent Trends in Civil Engineering and Built Environment, 2022)
For the past few decades, the invention and widespread usage of plastics for myriad daily applications which used to rely on conventional materials have been one of the major inventions. It is also have been manufactured with a wide range of material properties, enabling adaptation to many different applications, and was revolutionized in many industries for many different purposes. Therefore, this study is an idea to use the plastic modified asphalt for repairing potholes. Road distress like pothole may become worse if it is not repaired immediately. The objectives of this study are to study the strength of plastic modified asphalt for pothole repairing and to analyze the optimum plastic content (OPC) in the asphalt mixture. The study is focus on plastic waste materials that are often used in asphalt pavement. It is related with the performance of modified asphalt mix that use plastic waste as the additives in asphalt. The method used to conduct the study is systematic review. The relationship of plastic modified asphalt with the stability, tensile strength and resilient modulus were identified in the study. It has been proved that the plastic modified asphalt provides better stability, strength and resistance to the pavement. It is suggested to perform research of modified asphalt with various types of thermoplastic waste as it can be recycled and comes from variety of uses.